Limitations of fibrosis grade as diagnostic criteria for post polycythemia vera and essential thrombocytosis myelofibrosis. Issue 7 (July 2015) - Gowin, K.; Verstovsek, S.; Daver, N.; Pemmaraju, N.; Valdez, R.; Kosiorek, H.; Dueck, A.; Mesa, R.
Highlights PMF and post-PV/ET with grade 1 fibrosis examined. PV/ET manifest clinical progression toward post-PV/ET yet may fail to meet criteria. MPN progression represents a biological spectrum. Definitions of post ET/PV may benefit from criteria not restricted by fibrosis.